Milk Productivity of Black-Motley Cows with Easy and Troubled Calvings - Ramazanovich Feyzullayev, Feyzullah; Anatolyevich Babushkin, Vadim; Vladimirovich Bakai, Anatoly; Viktorovna Lepekhina, Tatiana (International Journal of Engineering and Technology, 2018)
During its formation and improvement, cattle acquired a number of biological and economic-useful qualities, which allowed identifying separate groups of animals with high productivity and productive longevity. One of the main criteria for cow selection for further breeding is the quantity and quality of dairy products [4]. Profitability of dairy farming largely depends on both milk yield and theÂ reproductive ability of cows. Troubled calving and subsequent diseases and complications affect the state of the animal organism; preservation and restoration of the health of a cow after troubled calving require considerable expenses. This research was aimed at examining milk production in cows with easy and troubled calving. To achieve this goal, in the studied number of cows with easy and troubled calving, the authors analyzed the following parameters: milk yield during the first lactation, fat and protein mass fraction, the amount of milk fat and milk protein; milk productivity was also studied, depending on the age at first insemination and theÂ duration of the service period. It has been found that milk yields in the cows with troubled calving were higher than in the cows with easy calving. The influence of the age at the first fruitful insemination on the further milk productivity has been determined: the highest yields were obtained from the cows with the age at the first fruitful insemination in theÂ interval between 15.1 and 17.0 months. The maximum milk yields during the first lactation â€“ 6,206 kg - were observed in the cows with relatively short service period (61 to 90 days).Â Â